ON THE PHONETICS OF ARSUZ DIALECT - Meltem GÜL (Fırat University, 2019)
Studies on Turkish dialects of Turkey have increased in recent years. Studies that have been conducted to investigate less or not studied regional dialects so far have been studied. The dialects that exist in Anatolia have improved only in terms of expression without the influence of the written language since settlement to these regions. This improvement shows itself in phonetics and morphology. From the earliest periods of Turkish to the present, the use of vowels has been in diverse ways. The same diverseness is manifested in Arsuz dialect too. It is observed that phonetics of the region such as À, ?, a, a°, ?, e, e°, í, ì, í, iˆ, ï, ?, o?, ÿ, u, u, o, üˆ, u, Ç, à ú, ğ´, `ğ, x, K, K?, l ?, ?, P, s, T, ?ˆ, r?, ?, ? are used to fulfil vowels in the dialect of the district. In this article, the basic features that determine the phonetics of the region are discussed. It has been studied to reveal the features that distinguish Arsuz dialect structure from written language besides the changes in grammatical structures due to sound changes. All subjects in Turkish morphology are investigated in Arsuz dialect and exemplified in details how they have changed. Due to the loss of dialects that are of great importance in terms of the history of Turkish language day by day, it is getting difficult to detect sound characteristics. It is thought that studying the basic features related to the use of vowels shaping Arsuz dialect together with the samples will contribute to dialect researches.